2018
DOI: 10.22631/ijbmph.2018.56097
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of antibiotic resistance of gram-negative bacteria isolated from urinary tract infections in patients referring to Neka laboratories-Iran

Abstract: Introductionrinary tract infection is an inflammatory response of the urethra to the invasion of pathogenic microorganisms (1). This infection is of the highest importance after respiratory tract infection and is the second most common infection in children and adults and the most important infection in infants. In the world, every year, 150 million people are affected by this infection, and includes 35% of hospital infections (2-4). Urinary tract infections are one of the most common infections that occur at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Zare et al [1] and Fajfr et al [7] reported that E. coli was the most predominant isolated pathogen (66.7%,.45 %,51.3%) respectively.This documented the principal role of E. coli in causing UTI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zare et al [1] and Fajfr et al [7] reported that E. coli was the most predominant isolated pathogen (66.7%,.45 %,51.3%) respectively.This documented the principal role of E. coli in causing UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infection (UTI) is considered one of the most frequent problems found in different clinical settings and accounts for about a quarter of all antimicrobial prescriptions. Every year, 150 million people worldwide are affected by this infection, including 35% of hospital infections [1]. Escherichia coli (E.coli) is the main pathogen responsible for uncomplicated cystitis and pyelonephritis, followed by other species of Enterobacteriaceae, such as Proteus mirabilis and mostly Klebsiella pneumoniae, Gram-positive pathogens, such as Enterococcus faecalis and Staphylococcus saprophyticus also may be included [2].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis was conducted by Aliyu et al and stated that among nursing home residents, Escherichia coli accounted for the largest proportion of multidrug-resistant gramnegative bacterial isolates [14]. Moreover, Zare et al reported that among gram-negative bacteria isolated from patients with urinary tract infections, the most commonly isolated bacteria in the urine included Escherichia coli (45%), Enterobacter (12%), Klebsiella (3.14%), and Pseudomonas isolates (1.22%) [15]. Additionally, saber et al and Gajdács et al reported that Escherichia coli has been documented to be the most common pathogen associated with urinary tract infections in many countries causing both community-and hospital-acquired UTI [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…UTIs are mainly the second most common infections bacterial after respiratory tract infections, seen in primary care. UTIs is a bacterial invasion-induced inflammatory reactions of the urothelium related to bacteriuria and pyuria [2]. Anatomically, divided of UTIs are into two portions, pyelonephritis is an upper urinary tract portion (ureters, renal pelvis, and kidneys), and cystitis is a lower urinary tract portion (urethra and urinary bladder) [3].…”
Section: Introductionmentioning
confidence: 99%